Assessment of Complications following Thyroid Surgery - Das, Sanjoy; Datta, Pranay Kumar (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background : Different diagnostic tools are available for assessment of post operative outcomes of thyroid surgery. This study was done to reach a consensus and to find out the best diagnostic tool for assessment of post operative complications of thyroid surgery. Materials and methods : A cross sectional study was carried out in the Medical Centre Hospital Between July 2016 to June 2017. Total 50 patients were included in the study, where post operative complications of patients were assessed, studied and enrolled. To assess the post operative outcomes of patients undergoing thyroid surgery. Data were analyzed and presented as both qualitative and quantitative data as applicable using SPSS version 20. The quantitative data were analyzed by mean, standard deviation. The qualitative data were analyzed by Mc NEMAR test (Mc NEMAR χ2 test). For all analytical test, the level of significance was set at 0.05 and p value equal or less then 0.05 was considered as significant, p value more than 0.05 was considered as not significant. Results : Fifty patients were selected for the study who were treated by Thyroidectomy. The mean patient's age at the time of surgery was 40.9±9.1 years ranged from 10 to 60 years. Data were collected in a prescribed data collection sheet. Then all data were compiled and analyzed. Result: 14% of the patients had complications, of them 2% had transient hypoparathyroidism, 4% had haemorrhage, 2% had temporary Recurrent Laryngeal Nerve (RLN) palsy and 2% had permanent recurrent laryngeal nerve palsy, 2% had Superior Laryngeal Nerve (SLN) palsy & 2% had wound infection. Improved surgical techniques and proper management of complications reduce the postoperative morbidity and mortality of thyroid surgery. Conclusions: Different types of complications may occur following thyroid surgery. In spite of all measures, keen observation in postoperative period is very important to find out the complications for early intervention. JCMCTA 2021 ; 32 (1) : 44-47